Effect of jet flow control in front of the leading bogie on the aerodynamic drag and underbody slipstream of high-speed trains - Sha Huang; Zhi-Wei Li; Wen-Jing Peng; Jin-Rong Lin; Zun-Di Huang; Guang-Zhi Zeng (Engineering Applications of Computational Fluid Mechanics)
Bogies are significant contributors to the aerodynamic resistance of high-speed trains, making them key areas of consideration for flow control and optimization. This study applied an air jet slot positioned in front of the leading bogie to explore its effectiveness in reducing the train’s aerodynamic resistance under Reynolds number (Re) of 2.64 × 106. The SST k-ω-based Improved Delayed Detached Eddy Simulation (IDDES) turbulence model was utilized to study the effects of various jet velocities and angles on the transient and time-averaged flow change underneath the train, as well as their correlations with aerodynamic drag reduction rates [Formula: see text]. Results indicate that the [Formula: see text] exhibits a notable upward trajectory with increasing jet velocity, followed by a slight decline once the jet velocity exceeds 0.8U (the train speed) at jet angles below 75°. Moreover, the increase of jet velocity results in a significant decrease in slipstream velocities but an increase in turbulent vorticity, intensity and kinetic energy underneath the leading bogie after the jet slot. The impact of jet angle is comparatively less pronounced than that of jet velocity, the disparity in drag reduction rates caused by varying jet angles remains within a range of 2.4% at a specific jet velocity, and the mean slipstreams and turbulent variables demonstrate minimal changes with varying jet angles. Optimal aerodynamic drag reduction is achieved with an air jet velocity of 0.8U and an angle of 15°, which is 6.43% for the whole train. The results presented in this paper suggest a new aerodynamic drag reduction method based on active flow control, providing engineering implications for the energy-efficient development of high-speed trains.